BASALT-INHERITED MICROLITES IN SILICIC MAGMAS: EVIDENCE FROM MOUNT PELÉE (MARTINIQUE, FRENCH WEST INDIES) - Martel C.; Ali A.R.; Poussineau S.; Pichavant M.; Gourgaud A. (My University, 2006)
During magma ascent in the volcanic conduit, the decompression of a silicic melt may result in the crystallization of morphologically and compositionally specific crystals, designated microlites. Hence, microlites have been considered as probes of mechanisms and time scales of magma ascent. Some microlites, however, appear to be in strong thermodynamic disequilibrium with their surrounding melt. We present here an experimental data set revealing that these microlites actually grew prior to ascent during mafic recharge of the magma chamber. Therefore, these microlites have no genetic relation to decompression-induced crystallization processes. Their presence may affect the rheological properties of the melt, as well as crystal growth mechanisms and kinetics during magma ascent. © 2006 Geological Society of America.
Keywords: BASALT; MAGMA MIXING; MELT; MICROLITE; RHYOLITE